Meningkatkan Kesiapan Dalam Mengimplementasikan Kurikulum Merdeka Melalui In House Trainning (IHT) Bagi Guru SMA Di Kabupaten Grobogan - Sumiat, Sumiat (Universitas Muria Kudus, 2022)
In House Training is aimed to increase the readiness in implementing Kurikulum Merdeka for high school teachers in Grobogan regency in academic year of 2022/2023. Kurikulum Merdeka in academic year of 2022/2023 for high school teachers in Grobogan regency runs well. The result of coordination among the writer, the principals, the curriculum team in three samples of construction schools: SMA Negeri 1 Purwodadi, SMA Negeri 1 Gabus, and SMA Kristen Purwodadi also the principal of SMA Negeri 1 Pulokulon as a task executor and collaborator in this school action research agreed that In House Training should be done as an effort to increase the readiness in implementing Kurikulum Merdeka in academic year of 2022/2023 for high school teachers in Groban regency. The result of School Action Research done by the writer is high school teachers in Grobogan regency are more ready and confident in implementing Kurikulum Merdeka in the beginning of academic year of 2022/2023 through In House Training given. In conclusion, through In House Training, there is a significant change in the increasing of Grobogan regency high school teachers’ readiness in implementing Kurikulum Merdeka. It is shown from the result of questionnaire given at the beginning of academic year 202/2023. The category changed from “not ready” or less than 25 percent to “ready” or 51-57 percent. As a result, it could be said that at the beginning of academic year 2022/2023, the high school teachers in Grobogan regency were ready and confident in implementing Kurikulum Merdeka.